Competitive Strategy of Banking Industry (Studies in Bengkulu Province) - AB, Syaiful Anwar (D-III Keuangan dan Perbankan, 2015)
The purpose of this study examines the competitive strategies tested the banking industry in the province of Bengkulu. Issues raised in this study is the extent the competitive strategy of banking and can ultimately increased customer. The aim to be achieved is to know what strategies can be applied. The analysis tool is to use qualitative paradigm mapping descriptive with banks in the province of Bengkulu with cluster analysis. Data collection method used in this study was secondary data collection and in-depth interviews. The results of this study conducted that the application of competitive strategy of Bank Rakyat Indonesia, Bank Mandiri, Bank Bengkulu and market penetration strategy was by opening a branch office network and cash office assistant sub-district area are yielded Â positive results. From the aspect of services offered, the customer feels that the diversification of services has been able to meet customer needs. The aspect of competitive strategy, distribution aspects of a positive assessment, especially the ease of access, is felt more quickly. Customers feel that the branch offices is still lack, particularly for the Bank are classified as market followers. Customers feel that the promotion is still lacking, particularly those Bank whose branches or cash office in the area. The Â strategy Â that may be used is a segmentation strategy, developing target market, and positioning.